A longitudinal study of renal function outcomes in a cohort of HIV patients on tenofovir-based antiretroviral therapy in Ashanti region, Ghana - E. Ahenkan; P. Kolibea Mante; E. Boakye-Gyasi (Infectious Diseases and Tropical Medicine, 2023)
OBJECTIVE: Tenofovir disoproxil fumarate (TDF), an integral component of first-line antiretroviral therapy (ART), is associated with nephrotoxicity, including a decline in glomerular filtration rate (GFR). The study describes renal function outcomes and risk factors for TDF-associated renal impairment in a Ghanaian cohort who had no known risk factors for renal impairment.